Tissue-specific tagging of endogenous loci in Drosophila melanogaster. - Koles, K.; Yeh, A.R.; Rodal, A.A. (Biology open, 2015)
Fluorescent protein tags have revolutionized cell and developmental biology, and in combination with binary expression systems they enable diverse tissue-specific studies of protein function. However these binary expression systems often do not recapitulate endogenous protein expression levels, localization, binding partners and/or developmental windows of gene expression. To address these limitations, we have developed a method called T-STEP (tissue-specific tagging of endogenous proteins) that allows endogenous loci to be tagged in a tissue specific manner. T-STEP uses a combination of efficient CRISPR/Cas9-enhanced gene targeting and tissue-specific recombinase-mediated tag swapping to temporally and spatially label endogenous proteins. We have employed this method to GFP tag OCRL (a phosphoinositide-5-phosphatase in the endocytic pathway) and Vps35 (a Parkinson's disease-implicated component of the endosomal retromer complex) in diverse Drosophila tissues including neurons, glia, muscles and hemocytes. Selective tagging of endogenous proteins allows, for the first time, cell type-specific live imaging and proteomics in complex tissues.